O Banco Mundial e as Orientações para a Educação Infantil No Brasil (2011-2019) - Bueno, Vivian Cristina (2020)
Brazilian childhood carries in its historical heritage a care assistance concept. The conception of childhood in the various historical moments, demonstrated the social value attributed to this age group and indicate the form and content of the organization of public educational assistance. Childhood education permeated social conflicts and conflicts within the class society. In Brazil, early childhood education becomes the right of all children, with the Federal Constitution enacted in 1988 and was inserted in the context of adjustments proposed by international organizations in discussions of the context of globalization, which permeated the Brazilian Education Reform process initiated in 1990. The international influence, in particular of the World Bank, guided guidelines for the sectorial adjustments implemented by the State Reform through the Master Plan (1995), as well as for the education sector, incurring countless changes regarding the education sector, based on the Human Capital Theory. The World Bank, as an agency that promotes loans aimed at supposedly boosting development and promoting political and social stability, dedicates itself more intensively to financing and technical assistance directed to projects in the educational area. In this sense, this work was intended, within the scope of educational policies for early childhood education, to investigate the main guidelines for early childhood education present in the National Education Plans 2001-2010 and 2014-2024, in the Curricular Guidelines for Early Childhood Education (2010) and in the National Common Curricular Base (2017) considering the guidelines of the World Bank and the guiding documents of the Reform of the Brazilian State. It was possible to identify in the documents studied and that refer to early childhood education, that they express the guidelines of the World Bank, with regard to teaching based on competences and skills, with privileged practical knowledge over scientific knowledge, valuing teaching while enabling instrument to meet the demands of the production process.